Screening Isolat Bacillus thuringiensis yang Berasal dari Karang Intan Kabupaten Banjar Kalsel terhadap Larva Nyamuk Aedes aegypti Instar 3 - Muhamat Muhamat (Bioscientiae, 2010)
This study aimed to obtain isolates of B. thuringiensis pathogenic to larvae of mosquitoes Ae. aegypti from various habitats of mosquitoes in Karang Intan of Banjar District, South Kalimantan. The sampling has been conducted as many as 38 bags, and then isolation of B. thuringiensis was performed until obtained 15 isolates. Pathogenicity screening of 15 isolates against third instar larvae at a concentration Ae. aegypti 1x109 ccs (complex crystal protein spora)/ml obtained two pathogenic isolates, i.e. isolates MA17 and MA25-1. LC50 and LC90 for isolate MA17 with 24 hours of treatment time respectively were 2.63x109 ccs/ml and 2.04x1010 ccs/ml. LC50 and LC90 for isolate MA17 with 48 hours of treatment time respectively were 3.55x108 ccs/ml and 8.27x109 ccs/ml. LC50 and LC90 for MA25-1 isolates with 24 hours of treatment time respectively were 1.29x1010 ccs/ml and 8.51x1010 ccs/ml. LC50 and LC90 for MA25-1 isolates with 24 hours of treatment time respectively 2.88x109 ccs/ml and 2.88x1010 ccs/ml.